Analysis of climatological variables, in two plant cover, from the central Andes, Colombia (Revista de Investigaciones Universidad del Quindío, 2023)
Between October 2014 and January 2021 was analyzed for climatological variables such as: air temperature (maximum and minimum), soil temperatures and relative humidity. In general, it was observed that the air temperature within the secondary forest had lows of 11°C and highs of 29.4°C; while in forest patches under restoration, differences were observed, below 12°C and close to 42°C. At maximum and minimum temperatures it was observed that the greatest oscillations were outside the secondary forest relict in patches under restoration (varying by 11°C, mean of 16.9°C vs. by 10°C, average of 16°C within the forest). The soil temperature is higher in patches under restoration and outside the forest (mean 18.2°C) than inside (mean 16.8°C), except in 2018; however, its variation overlaps in both sampling stations (outside 10.0-29.0°C and inside 11.0-25.0°C). Relative humidity was found to be higher (average 75.6%) within the secondary forested relict than outside in patches under restoration (average 71.4%); also within the secondary forested relict, values were observed between 28.0% and 100%, outside the forest in patches under restoration variations between 18.0% and 99.0% were noted, relative humidity data close to 20% were recorded in 2018, and close to 90-100% in 2019.
Keywords: Temperatures; Relative Humidity; Anthropic Effect; Mountain; Neotropics